Avaliaçäo da Determinação da Fibra em Detergente Neutro e da Fibra em Detergente Ácido pelo Sistema ANKOM - Berchielli, Telma Teresinha [UNESP] (2001)
The ANKOM filter bag system was compared with the conventional filtration system (Van Soest) to determine acid detergent fiber (ADF) and neutral detergent fiber (NDF) in different materials. In the first experiment five feeds (sugar cane, Marandu grass - Brachiaria brizantha cv. Marandu, corn silage, citrus pulp and cattle feces) and four types of filter bags were compared. A completely randomized block design in a factorial scheme (5x4), with three replications, was used. The means obtained by the ANKOM system were compared with those obtained by the conventional filtration procedure. The sample amount effect (0.5; 0.8; 1.0 g) in each filter bag on ADF and NDF contents was studied in the second experiment, using three feeds and the ANKOM system. In this experiment, a completely randomized blocks design, in a factorial scheme (three feeds x three amount feed) and three replications, was used. The types of filter bag did not affect the NDF content of the different feeds, except for feces, which bags showed smaller NDF contents. There were no statistical differences among NDF or ADF values determined either by the ANKOM or by the conventional filtration procedures for most of the feeds used, except citrus pulp, which had lower ANKOM- ADF values than the conventional procedure. The sample amount did not affect the NDF of the feed determined by the ANKOM System.